2020
DOI: 10.1016/s2666-7568(20)30015-5
|View full text |Cite
|
Sign up to set email alerts
|

Circadian disturbances in Alzheimer's disease progression: a prospective observational cohort study of community-based older adults

Abstract: Background Circadian disturbances are commonly seen in people with Alzheimer's disease and have been reported in individuals without symptoms of dementia but with Alzheimer's pathology. We aimed to assess the temporal relationship between circadian disturbances and Alzheimer's progression. MethodsWe did a prospective cohort study of 1401 healthy older adults (aged >59 years) enrolled in the Rush Memory and Aging Project (Rush University Medical Center, Chicago, IL, USA) who had been followed up for up to 15 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 31 publications
8
101
1
1
Order By: Relevance
“…On the other hand, we also unexpectedly found that older adults had more stable and less fragmented RAR than younger adults. This result is seemingly at variance with evidence of decreases in stability and increases in fragmentation relating to age-related neurodegenerative disorders, such as Parkinson’s disease [ 43 ] and Alzheimer’s disease [ 11 , 13 ]. However, the association between circadian rhythms and neurodegenerative disease has been reported to be bidirectional, with neurodegenerative disease also affecting circadian rhythms [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, we also unexpectedly found that older adults had more stable and less fragmented RAR than younger adults. This result is seemingly at variance with evidence of decreases in stability and increases in fragmentation relating to age-related neurodegenerative disorders, such as Parkinson’s disease [ 43 ] and Alzheimer’s disease [ 11 , 13 ]. However, the association between circadian rhythms and neurodegenerative disease has been reported to be bidirectional, with neurodegenerative disease also affecting circadian rhythms [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 92%
“…Another longitudinal analysis of 2930 older men also reported that, compared with participants in the highest quartile of amplitude, mesor (mean activity level) and pseudo-F statistic, those who were in the lowest quartiles had nearly three times greater risk of developing Parkinson disease [ 9 ]. Risk of dementia or mild cognitive impairment have also been associated with decreased amplitude or delayed acrophase [ 10 , 11 ]. Metrics of RAR irregularity such as decreased interdaily stability (IS, day-to-day stability of RAR) and increased intradaily variability (IV, fragmentation of RAR) have been linked with increased risk of cardiometabolic disorders [ 12 ], neurodegenerative diseases [ 3 , 13 ], and mortality [ 14 16 ], thus underscoring the critical role of RAR for human health.…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies of circadian rhythms demonstrate reduced stability and increased fragmentation with age, these changes accelerate with diagnosis of MCI or AD and fasten the transition between the two (49). Critical biochemical and behavioral changes appear to work bi-directionally between sleep and neurodegeneration, although the precise temporal dynamics are unknown (50).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies, using standard nonparametric RAR measures, have reported altered RARs among older adults across the spectrum of AD. Overall, such work has shown that older adults exhibit reduced rhythm amplitude, and less stable, more fragmented rhythms, that become increasingly abnormal among those with MCI and after the onset of dementia [ 27 ]. These metrics do not, however, provide information about any shifts that may occur in the temporal details of the 24-hour circadian profile.…”
Section: Discussionmentioning
confidence: 99%